Substitutive effects of accounting transparency and corporate governance on firm value - Gil, Jangho; Hwang, Heeju (International Journal of Management and Sustainability, 2024)
Recently, there has been increasing emphasis on the importance of accounting transparency and corporate governance. While previous studies have individually examined their impact on firm values, this paper investigates their combined effects. Using data from the Compustat and Center for Research in Security Prices databases obtained through Wharton Research Data Services, we measure accounting transparency and company value, and we employ the E-index as a measure of corporate governance. This study conducts firm, year, and industry fixed effects regressions on a large panel dataset comprising 21,476 firm-year observations. According to our research, both accounting transparency and good corporate governance have negative effects on the value of a company. This means that spending money to improve both may end up costing more than it benefits, which could lower the value of the company. These results support the notion that investors may see that maintaining high levels of accounting transparency and corporate governance can be excessively costly, while an overemphasis on these two metrics could potentially limit the flexibility and creativity of management. These findings have implications for managers tasked with achieving a balance between robust corporate governance, enhanced accounting transparency, and corporate value considerations.